Anti‐platelet therapy: ADP receptor antagonists - Wijeyeratne, Yanushi Dullewe; Heptinstall, Stan (British journal of clinical pharmacology, 2011)
The P2Y12 receptor on platelets with which ADP interacts has an important role in promoting platelet function and thereby platelet involvement in both haemostasis and thrombosis. Agents that act as antagonists at this receptor are thus likely to provide effective antithrombotic therapy, provided that there are no adverse effects on haemostasis. Here we describe the ADP receptor antagonists that are available and in development. We also consider their mode of action and ask whether there are additional mechanisms through which they exert their inhibitory effects on platelet function.